68Ga-EMP-100 PET/CT—a novel ligand for visualizing c-MET expression in metastatic renal cell carcinoma—first in-human biodistribution and imaging results. - Mittlmeier, Lena M.; Todica, Andrei; Gildehaus, Franz-Josef; Unterrainer, Marcus; Beyer, Leonie; Brendel, Matthias; Albert, Nathalie L.; Ledderose, Stephan T.; Vettermann, Franziska J.; Schott, Melanie; Rodler, Severin; Marcon, Julian; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2022)
Background: 68Ga-EMP-100 is a novel positron emission tomography (PET) ligand that directly targets tumoral c-MET expression. Upregulation of the receptor tyrosin kinase c-MET in renal cell carcinoma (RCC) is correlated with overall survival in metastatic disease (mRCC). Clinicopathological staging of c-MET expression could improve patient management prior to systemic therapy with for instance inhibitors targeting c-MET such as cabozantinib. We present the first in-human data of 68Ga-EMP-100 in mRCC patients evaluating uptake characteristics in metastases and primary RCC. Methods: Twelve patients with mRCC prior to anticipated cabozantinib therapy underwent 68Ga-EMP-100 PET/CT imaging. We compared the biodistribution in normal organs and tumor uptake of mRCC lesions by standard uptake value (SUVmean) and SUVmax measurements. Additionally, metastatic sites on PET were compared to contrast-enhanced computed tomography (CT) and the respective, quantitative PET parameters were assessed and then compared inter- and intra-individually. Results: Overall, 87 tumor lesions were analyzed. Of these, 68/87 (79.3%) were visually rated c-MET-positive comprising a median SUVmax of 4.35 and SUVmean of 2.52. Comparing different tumor sites, the highest uptake intensity was found in tumor burden at the primary site (SUVmax 9.05 (4.86–29.16)), followed by bone metastases (SUVmax 5.56 (0.97–15.85)), and lymph node metastases (SUVmax 3.90 (2.13–6.28)) and visceral metastases (SUVmax 3.82 (0.11–16.18)). The occurrence of visually PET-negative lesions (20.7%) was distributed heterogeneously on an intra- and inter-individual level; the largest proportion of PET-negative metastatic lesions were lung and liver metastases. The highest physiological 68Ga-EMP-100 accumulation besides the urinary bladder content was seen in the kidneys, followed by moderate uptake in the liver and the spleen, whereas significantly lower uptake intensity was observed in the pancreas and the intestines. Conclusion: Targeting c-MET expression, 68Ga-EMP-100 shows distinctly elevated uptake in mRCC patients with partially high inter- and intra-individual differences comprising both c-MET-positive and c-MET-negative lesions. Our first clinical results warrant further systemic studies investigating the clinical use of 68Ga-EMP-100 as a biomarker in mRCC patients.